Construction Planning, Equipment, and Methods, Ninth Edition - Peurifoy, Robert L.; Schexnayder, Clifford J.; Schmitt, Robert; Shapira, Aviad (McGraw-Hill Education, 2018)
Fully updated coverage of construction planning techniques and equipment technology. Construction Planning, Equipment, and Methods, Ninth Edition, follows in the footsteps of previous editions by laying out the fundamentals of machine utilization and production estimating in a logical, simple, and concise format. The book discusses the latest technologies and capabilities and offers real-world applications. Examples and illustrations showcase the newest equipment models, and end-of-chapter summaries and homework problems reinforce salient points. You will explore construction economics, earthwork, and soil and rock properties.